1984
DOI: 10.3189/s0022143000006201
|View full text |Cite
|
Sign up to set email alerts
|

The Shear Strength Characteristics of Frozen Coarse Granular Debris

Abstract: ABSTRACT. The effect of ice con ten t a nd normal load on the shear strength charac te rist ics ora frozen coarse g ra nul a r debris was in ves ti g ated . 3 1 shear tests were carr ied out in a modified shea rbox all owing a sampl e te mperat ure of t -1. 0 ± 0.2 j" C and a load rate of 9.63 x 10 -4 cm/min . Th e tes ts showed tha t as the ice co nten t of the frozen d eb ris was increased from 0 % (undersaturated ) to 25 % (saturated), sample shear strength was ma rkedl y increased. In contrast, sample shea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 12 publications
3
22
0
Order By: Relevance
“…Subsequent work extended the range of debris and ice concentrations to ice‐rich and ice‐poor debris and indicated that the composite reached a peak strength at high debris concentration but became weaker as the mixture became more ice‐poor [ Baker , ]. A similar result was found in higher‐temperature direct shear experiments on undisturbed rock glacier material from the Yukon, Canada, though the relative increase in strength was subdued compared to colder experiments [ Nickling and Bennett , ]. In most of these experiments, the peak strength corresponded to a relatively high debris concentration and when the pore spaces were completely filled with ice, and this strength was only weakly sensitive to the rate of deformation for temperatures below −5°C [ Baker , ; Parameswaran , ; Baker and Jones , ].…”
Section: Experimental Constraintssupporting
confidence: 65%
“…Subsequent work extended the range of debris and ice concentrations to ice‐rich and ice‐poor debris and indicated that the composite reached a peak strength at high debris concentration but became weaker as the mixture became more ice‐poor [ Baker , ]. A similar result was found in higher‐temperature direct shear experiments on undisturbed rock glacier material from the Yukon, Canada, though the relative increase in strength was subdued compared to colder experiments [ Nickling and Bennett , ]. In most of these experiments, the peak strength corresponded to a relatively high debris concentration and when the pore spaces were completely filled with ice, and this strength was only weakly sensitive to the rate of deformation for temperatures below −5°C [ Baker , ; Parameswaran , ; Baker and Jones , ].…”
Section: Experimental Constraintssupporting
confidence: 65%
“…Tests using samples prepared by mixing crushed ice, water at 0 °C and soil yielded results similar to those of Baker () (e.g. Goughnour and Andersland, ; Nickling and Bennett, ). Arenson et al .…”
Section: Introductionsupporting
confidence: 70%
“…Very few rheological experiments have been reported on debris-bearing ice, and these have yielded diverse and sometimes contradictory results. Work on different types of debris-bearing ice led to the conclusion that the presence of debris could either strengthen or soften the ice, depending on the concentration, granulometry, and distribution of debris particles [e.g., Holdsworth, 1974;Nickling and Bennett, 1984;Echelmeyer and Zhongxiang, 1987;Waller and Hart, 1999;Fitzsimons et al, 2001]. A hint to our question here may be given by strain experiments on basal ice samples from Taylor Glacier.…”
Section: Rheological Contrastsmentioning
confidence: 99%